Role of intralesional bleomycin in recurrent or residual keloids and hypertrophic scars - Mishra, Bharat; Arora, Chetna (International Surgery Journal, 2021)
Background: Keloids and hypertrophic scars are difficult to treat. There are many modalities available with variable success rate. Triamcinolone is still the most commonly used drug but recurrence and partial response to this conventional treatment is still a major concern. Many studies have proved the role and efficacy of intralesional bleomycin and this study was done to assess the role of intralesional bleomycin in recurrent and residual lesions. Methods: The patients with recurrent lesion or residual lesions after the injection of triamcinolone were enrolled in the study. Patients received local infiltration of bleomycin. The injections were scheduled at monthly intervals for three consecutive months. They were followed at 1st, 2nd, 3rd, and 12th months. Scar assessment was done by calculating its volume, Vancouver scar scale (VSS) and visual analogue score (pain and pruritis). Side effects were also recorded. Final assessment was done at 1year for any recurrence. Results: Twenty-five patients completed the study. The most common location of scars was presternal (52%) and trauma was the most common cause in scars (20%). We observed the decrease of volume of 75.85% which was highly significant on statistical analysis (p=0.001). Similarly, statistically significant difference was noticed in VSS, VAS for pain and pruritis. No systemic side effects were noticed. No recurrence was noted at the end of 12 months. Conclusion: Intralesional bleomycin is found to be useful in management of recurrent or residual lesions. It can be a potential option in the management of recurrent and residual hypertrophic scars and keloids.